2014
DOI: 10.1177/1758573214560258
|View full text |Cite
|
Sign up to set email alerts
|

Management of glenohumeral synovitis secondary to influenza vaccination

Abstract: Glenohumeral synovitis is a rare complication of vaccination that can lead to shoulder dysfunction and prolonged pain. We report a case of florid glenohumeral synovitis after routine influenza vaccination, which we consider to have occurred because of the unintentional injection of antigenic material into synovial tissues, resulting in an immunemediated inflammatory reaction. We provide a review of the literature for this condition and describe an invasive management approach, providing, for the first time, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(41 citation statements)
references
References 8 publications
0
36
0
5
Order By: Relevance
“…The additional MRI findings in these prior reports included rotator cuff tendinosis and tendon tears. 5,9,10,12,15,16,20 Our case is unique in that progressive erosive changes were demonstrated along with an increase in severity of changes suggesting bursitis, synovitis, and adhesive capsulitis on serial examinations over a 6-month period. In addition, subsequent stabilization of osseous erosions was evident on radiographic follow-up 32 months later, after the resolution of symptoms.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…The additional MRI findings in these prior reports included rotator cuff tendinosis and tendon tears. 5,9,10,12,15,16,20 Our case is unique in that progressive erosive changes were demonstrated along with an increase in severity of changes suggesting bursitis, synovitis, and adhesive capsulitis on serial examinations over a 6-month period. In addition, subsequent stabilization of osseous erosions was evident on radiographic follow-up 32 months later, after the resolution of symptoms.…”
Section: Discussionmentioning
confidence: 77%
“…Subsequently, there have been a few published case reports and small series for a total of 25 cases describing the MRI findings of prolonged postvaccination shoulder injury. 5,[9][10][11][12][13] Fourteen of the 25 cases documented the MRI findings of bursitis, 5,12,[14][15][16][17][18][19] and 10 cases demonstrated bone marrow edema in the humeral head, 5,[10][11][12]14,16,[18][19][20] 8 of which followed influenza vaccination. Only 4 previous cases have demonstrated bone erosion on MRI after vaccination, 10,11,19,20 3 of which followed influenza vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…Our patient developed shoulder pain shortly after vaccination, possibly due to her vaccine being administered inadvertently higher than recommended (Fig. 3 ) [ 4 , 7 ]. Atanasoff and colleagues, in a retrospective study about SIRVA, reported that in 93% of the cases, shoulder pain occurred less than 24 h after vaccination and immediately following injection in 54% [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…This adverse reaction can also be caused when the injection is too deep, going through the muscle and into the bursa [ 4 , 7 , 8 , 10 ]. Bodor and Montalvo found that the subdeltoid bursa extended from 3.0 to 6.0 cm beyond the lateral border of the acromion at a depth from 0.8 to 1.6 cm [ 7 ] which could be easily reached by the 2.5-cm (1-in.)…”
Section: Discussionmentioning
confidence: 99%
“…Local adverse reactions to vaccinations most commonly include redness, swelling, and pain at the injection site. There are reported cases of shoulder injury related to vaccine administration (SIRVA) 2‐7 . Poor injection technique may result in certain shoulder‐related adverse events, such as bursitis or tendonitis.…”
Section: Introductionmentioning
confidence: 99%